Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/jacs.1c13067
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hypoxia-Induced Supramolecular Perylene Diimide Radical Anions in Tumors for Photothermal Therapy with Improved Specificity

Abstract: Considering that hypoxia is closely associated with tumor proliferation, invasion, metastasis, and drug resistance, it is of great significance to overcome hypoxia in tumor treatment. Herein, we report a hypoxia-induced specific photothermal therapy (PTT) based on the photothermal agent of supramolecular perylene diimide radical anions. Hypoxic regions in various tumors display strong reductive ability, and in such environments the supramolecular complex of a perylene diimide derivative and cucurbit [7]uril co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 61 publications
2
98
0
Order By: Relevance
“…PDI derivatives have been recognized as an ideal π-conjugated system for chemical, colorimetric and fluorescent sensors [ 12 , 13 ], organic semiconductors and optoelectronic devices [ 14 , 15 , 16 ], phototheranostics, [ 17 , 18 ] as well as bioimaging and gene/drug delivering agents [ 19 ]. Structurally, the PDI molecule is composed of one rigid, planar, and stable perylene core with two imide groups at both ends of the polycyclic aromatic scaffold.…”
Section: Synthesis and Properties Of Pdi Derivativesmentioning
confidence: 99%
“…PDI derivatives have been recognized as an ideal π-conjugated system for chemical, colorimetric and fluorescent sensors [ 12 , 13 ], organic semiconductors and optoelectronic devices [ 14 , 15 , 16 ], phototheranostics, [ 17 , 18 ] as well as bioimaging and gene/drug delivering agents [ 19 ]. Structurally, the PDI molecule is composed of one rigid, planar, and stable perylene core with two imide groups at both ends of the polycyclic aromatic scaffold.…”
Section: Synthesis and Properties Of Pdi Derivativesmentioning
confidence: 99%
“…[18][19][20][21][22] Compared with traditional "always-on" photothermal agents, activatable photothermal agents will suppress cancer precisely and minimize side effects on normal tissue. Although it has been reported that various photothermal reagents can be activated by the tumor microenvironment (hypoxia, [23][24][25] lower pH, [26][27][28][29] overexpression of biological enzymes, [30][31][32] and reactive oxygen species (ROS) [33][34][35] ),the majority of them have a signicant shortcoming: heavy spectral overlap between the photothermal agents and their corresponding products. That is, they are unable to achieve true selective activation and minimize side effects on adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, their electron-poor character renders them excellent electron acceptors that can produce stable radical anions. [3] These properties make PDIs promising materials as organic electron-transporting materials (by electron-hole transfer) [4][5][6][7][8] , for water splitting (by electron-transfer) [9,10] , as nearinfrared absorber in photothermal therapy [11][12][13][14] , or as photocatalysts [15,16] . In an example of the latter, König and coworkers showed that a PDI derivative could reduce aryl halides under inert conditions in DMF or DMSO upon photoexcitation of the radical anion state (PDI •-), [15] though the exact mechanism remains to be resolved.…”
mentioning
confidence: 99%